OP0082 Infections of The Gut, Urogenital and Respiratory Tract and Appendicitis during Childhood, and The Risk of Developing Ankylosing Spondylitis. (15th July 2016) - Lindström, U.; Exarchou, S.; Lie, E.; Dehlin, M.; Forsblad-d'Elia, H.; Askling, J.; Jacobsson, L.T.H.
Abstract : Background: Data supporting the role of specific environmental exposures in the development of AS are scarse. Microbial exposure, both in the form of infections and gut flora, has been implicated in the pathogenesis of several spondyloarthritis related conditions, such as reactive arthritis and inflammatory bowel disease (IBD). Gut dysbiosis has also been recognized in ankylosing spondylitis, but it is not known if this is a result of the disease or occurs before disease onset. Objectives: To determine if infections during childhood, primarily gut, urogenital and respiratory tract infections (RTI) as well as appendicitis, predict a diagnosis of AS. Methods: This is a register based study using several national registers. All individuals having ≥1 visit to specialized health care with an associated ICD-code for AS were identified in the national health care register, 1964–2009. For each index case 5 matched controls (sex, age, county) were retrieved from the population register. Cases and controls were linked to the National Patient Register (NPR) to identify hospitalization with an ICD-code indicating an infection (gastrointestinal, urogenital, respiratory tract or appendicitis) at an age of 0–16 years. In order to ensure complete exposure information only cases and controls living in Sweden up until their 17th birthday were included. In order to increase the likelihood of a temporal relationship all cases and controls with any diagnosis of a rheumatic disease, psoriasis, IBD or iridocyclitis before the age of 17 and juvenile idiopathic arthritis ever were excluded. Univariate conditional logistic regression analyses were used to determine odds ratios (OR) with confidence intervals (CI) for development of AS, with regard to the infectious exposures. Results: Based on 2643 cases with AS and 11064 matched controls, childhood appendicitis reduced the odds for a later diagnosis of AS by 40% and hospitalization with a RTI increased the odds by 20%. Hospitalization for urogenital or gastrointestinal tract infections did not predict an AS diagnosis (Table 1 ). Similar (and statistically significant) results were obtained when excluding all cases/controls with a diagnosis of IBD up until 2 years after the first AS-diagnosis of the index case. The trend was stronger for men than women (data not shown). Conclusions: Appendicitis during childhood decreased and RTI increased the risk of developing AS in this case-control study. Appendicitis/appendectomy has previously, repeatedly, been described to decrease the risk for ulcerative colitis, but has not been investigated for AS. Our findings suggest that early immune phenotype, either affecting the risk for severe childhood infections, or being modulated by such infections, may represent an early pathophysiological phase of AS. Disclosure of Interest: U. Lindström: None declared, S. Exarchou: None declared, E. Lie Grant/research support from: Personal fees from AbbVie, Bristol-Myers Squibb, Hospira, Pfizer, UCB, M. Dehlin: None declared, H. Forsblad-d'Elia: None declared, J. Askling Grant/research support from: JA and the ARTIS Study Group has or has had agreements with: AstraZeneca, Pfizer, UCB, Roche, Merck, BMS and Abbvie, L. Jacobsson: None declared